Occupational health hazards and causative factors of male adult bonded labourers of South India: a mixed method pilot study - Arunkumar, A. (International Journal Of Community Medicine And Public Health, 2017)
Background: Global slavery index estimates 35.9 million people in slavery today. There are no published studies that explore the various health issues faced by bonded laborers, their health seeking behavior, their access to healthcare facilities and healthcare providers. Methods:From January 2008 to March 2008, we developed a 61-item questionnaire that captures information on: socio-demographic characteristics, anthropometry, debt/bondage, work culture, socio-economic conditions and health status of the bonded labourers. The questionnaire was field tested and revised. Simultaneously a topic guide was developed for in-depth interviewing of selected participants. From April 2008 to July 2008, a total of 50 male adult bonded labourers were purposively sampled and recruited through the international non-governmental organization in Tiruvallur and Chengalpattu districts of Tamilnadu and Nagiri on the border of Tamil Nadu- Andhra Pradesh. Participants were from more than 35 rice mills and brick kilns of Tamil Nadu and Andhra-Pradesh. Twenty participants were selected for in-depth interviewing to expand on and explain the quantitative findings by listening to the narratives and lived experiences of these participants supplemented by five interviews from key informants who closely worked with the bonded laborers. Results: They face numerous health hazards owing to their slavery. It is observed that they do not have acceptable living conditions with very low salary, poor sanitary conditions, and inadequate knowledge of healthy life styles and low accessibility to health care providers. Conclusions:Structural and institutional policies are required to address the health issues of these bonded labourers. More studies are necessary to gain more insight on the health hazards faced by the bonded labourers of other parts of the country.